2016
DOI: 10.1108/jbim-07-2014-0139
|View full text |Cite
|
Sign up to set email alerts
|

How does word of mouth affect customer satisfaction?

Abstract: Purpose Although word of mouth (WOM) affects customers’ purchasing intentions to a large extent, prior research has neglected the role of WOM as a driver of customer satisfaction. Design/methodology/approach Several scholars have suggested that WOM can not only affect customer expectation but also can influence perceived quality. Consistent with existing research results and the expectancy disparity model, this paper established a causal relation between WOM and customer satisfaction and confirmed it was dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 31 publications
1
22
0
11
Order By: Relevance
“…We originally hypothesized that conformism would be seen in ants, whereby social information suggesting a high-value resource (a strong pheromone trail) would increase the perceived value of this resource, since such effects are strong in humans ( Cohen and Golden, 1972 ; Bone, 1995 ; Shi et al, 2016 ; Jayles et al, 2017 ), as long as the difference between the social ratings and the absolute value of the product is small. Recent research has found many parallels between value perception in humans and insects ( Shafir et al, 2002 ; Sasaki and Pratt, 2011 ; Tan et al, 2015 ; Czaczkes et al, 2018 ; Oberhauser and Czaczkes, 2018 ; Wendt et al, 2019 ), even resulting in irrational behavior, suggesting that a further parallel was likely.…”
Section: Discussionmentioning
confidence: 99%
“…We originally hypothesized that conformism would be seen in ants, whereby social information suggesting a high-value resource (a strong pheromone trail) would increase the perceived value of this resource, since such effects are strong in humans ( Cohen and Golden, 1972 ; Bone, 1995 ; Shi et al, 2016 ; Jayles et al, 2017 ), as long as the difference between the social ratings and the absolute value of the product is small. Recent research has found many parallels between value perception in humans and insects ( Shafir et al, 2002 ; Sasaki and Pratt, 2011 ; Tan et al, 2015 ; Czaczkes et al, 2018 ; Oberhauser and Czaczkes, 2018 ; Wendt et al, 2019 ), even resulting in irrational behavior, suggesting that a further parallel was likely.…”
Section: Discussionmentioning
confidence: 99%
“…The existance of negative WOM as the impact of service failure in this competitive world can be avoided by the service provider. The negative WOM can influence the consumer's satisfaction through the decline of their expectation of the product or service (Shi, Tang, Zhang, Gao, & Zhu, 2016). These two types of WOM come from customer experience and understanding of the brand (Casidy & Shin, 2015).…”
Section: Word-of-mouthmentioning
confidence: 99%
“…Hasil penelitian ini sesuai dengan rumusan hipotesis yang menyatakan bahwa customer satisfaction berpengaruh positif dan signifikan terhadap WOM pada konsumen produk H&M di Kota Denpasar yang artinya semakin baik customer satisfaction H&M maka akan membuat semakin tinggi tingkat penyebaran WOM positif mengenai produk H&M di Kota Denpasar. Hasil penelitian ini mendukung penelitian yang dilakukan oleh Carpenter & Fairhurst (2005), Roy et al (2014), Shi et al (2016) dan Blasco et al (2017) Uji Hasil perhitungan didapatkan perbandingan nilai Z hitung sebesar 5,701 > Z tabel sebesar 1,96, maka H4 diterima yang artinya customer satisfaction mampu memediasi secara signifikan pengaruh brand image terhadap WOM. Hal ini menunjukkan bahwa jika brand image yang dirasakan tersebut meningkat maka akan meningkatkan customer satisfaction, apabila customer satisfaction tersebut meningkat maka secara tidak langsung akan meningkatkan intensitas penyebaran WOM positif pada konsumen produk H&M. Berdasarkan perhitungan dari Pengaruh Brand Image (X) Melalui Customer Satisfaction (M) terhadap WOM (Y) diatas diperoleh Nilai VAF sebesar 37,5%, nilai ini berada di antara 20 persen hingga 80 persen, maka dapat dikategorikan sebagai pemediasi parsial (partial mediation).…”
Section: Tabel 1 Major Global Apparel Manufacturer and Retailerunclassified